Evaluating ICT Integration in Turkish K-12 Schools through Teachers' Views - Aydin, Mehmet Kemal; Gurol, Mehmet; Vanderlinde, Ruben (EURASIA, 2016)
The current study aims to explore ICT integration in Turkish K-12 schools purposively selected as a representation of F@tih and non-F@tih public schools together with a private school. A convergent mixed methods design was employed with a multiple case strategy as such it will enable to make casewise comparisons. The quantitative data was collected through e-capacity measurement scales. Concurrently, the qualitative data was gathered through three open-ended questions. The evaluation results illustrate that a private school outperformed all public schools, including F@tih and non-F@tih schools. However there are some promising results indicating that F@tih project has made some significant inroads into improvement of ICT related school conditions, specifically ICT infrastructure of public schools. Yet, the findings also illustrate that ICT coordination and support, ICT vision, policy and teachers' ICT training, and their ICT use are policy domains that should be addressed and improved in both F@tih and non-F@tih schools.
Keywords: e-capacity framework; F@tih project; ICT integration; multiple case study; program evaluation; TECHNOLOGY INTEGRATION; POLICY; MODEL; EDUCATION; TURKEY; Education & Educational Research